2007
DOI: 10.1016/j.bbabio.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of heme and heme–hemopexin with an extracellular oxidant system used to measure cell growth-associated plasma membrane electron transport

Abstract: Since redox active metals are often transported across membranes into cells in the reduced state, we have investigated whether exogenous ferri-heme or heme bound to hemopexin (HPX), which delivers heme to cells via receptor-mediated endocytosis, interact with a cell growth-associated plasma membrane electron transport (PMET) pathway. PMET reduces the cell-impermeable tetrazolium salt, WST-1, in the presence of the mandatory low potential intermediate electron acceptor, mPMS. In human promyelocytic (HL60) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…DMSO was used as a vehicle control, such that the same volume of vehicle was added to all treatment groups. Hemin chloride was dissolved in DMSO and verified to be in the monomeric form by measuring the absorbance at 406 nm (⑀ ϭ 170 mM/cm) (73). Hemin was added directly from the DMSO stock to the medium before addition to cells.…”
Section: Methodsmentioning
confidence: 99%
“…DMSO was used as a vehicle control, such that the same volume of vehicle was added to all treatment groups. Hemin chloride was dissolved in DMSO and verified to be in the monomeric form by measuring the absorbance at 406 nm (⑀ ϭ 170 mM/cm) (73). Hemin was added directly from the DMSO stock to the medium before addition to cells.…”
Section: Methodsmentioning
confidence: 99%
“…In a paper by Rish et al [32] it was demonstrated that highly proliferative cells are characterized by a plasma membrane electron transport (PMET) that enables cells to transfer electrons from intracellular reductants, like NADH, to extracellular electron acceptors. Among electron acceptors, Rish et al indicated the heme-Hx complex as one of the best physiological candidates for this function.…”
Section: Discussionmentioning
confidence: 99%
“…93 PMOR is measured using two substrates: reduction of the water soluble tetrazolium salt, WST-1 [2,(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium), in the presence of an intermediate electron acceptor [IEA; mPMS (1-methoxy-5-methylphenazinium methylsulfate)] 92 The redox potential of heme-HPX is ~50mV, and evidence that heme-HPX is a substrate for PMOR has been obtained in human promyelocytic HL60 cells and linked to the LRP1-independent low-affinity, high-capacity uptake system of heme-HPX. 3,19 Additional evidence links PMOR/PMET and redox cycling of copper with heme-HPX endocytosis. 19 If there is incomplete reduction of oxygen, then an oxidase component may generate superoxide from which H 2 O 2 is derived.…”
Section: Mechanisms For Heme Release From Hpxmentioning
confidence: 98%
“…3,19 Additional evidence links PMOR/PMET and redox cycling of copper with heme-HPX endocytosis. 19 If there is incomplete reduction of oxygen, then an oxidase component may generate superoxide from which H 2 O 2 is derived. In the presence of reduced copper or iron, the hydroxyl radical and carbonyls will be produced.…”
Section: Mechanisms For Heme Release From Hpxmentioning
confidence: 98%
See 1 more Smart Citation